2-2-(-7)=

Simple and best practice solution for 2-2-(-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2-(-7)= equation:


Simplifying
2 + -2 + -1(-7) = 0

Multiply -1 * -7
2 + -2 + 7 = 0

Combine like terms: 2 + -2 = 0
0 + 7 = 0
7 = 0

Solving
7 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 52=4d | | 60=5y | | 5(-2n+4)= | | (-8)+2+1= | | 8.6=n+2.2 | | 27=3x-15+18 | | -5(x-2)+3x=10-4(2x-5)+6 | | 2/11n=-3/8 | | 3x-3=3(x+1)+6 | | X+3x/120 | | 2m-3=-8m+27 | | x^4-2x^3+15x^2=0 | | -1-5x=-36 | | Z+5=8 | | 20-13=20+9x | | 1.3+0.5x=-3.14 | | 8^2+9(12/3*2)-7 | | 16/8=n/36 | | (3)(2)/2-4 | | -6x+1=7-6x | | 153/24 | | 9(v+1)-3v=2(3v+1)-5 | | 1.3c=3c+2.8 | | B-8+6b=24 | | 3(x-3)=6x-18/2 | | 5(2.4-4)=8 | | 568-507x=567 | | 4(-15)=13-6(4) | | -7(7x+6)-3(x-9)= | | 7=-5+6(-8x+2) | | -11=3x+7-3x | | 5y-11-2y^9=0 |

Equations solver categories